1991
DOI: 10.5271/sjweh.1694
|View full text |Cite
|
Sign up to set email alerts
|

Spectral analysis of sleep electroencephalography in rotating three-shift work.

Abstract: , MD3AKERSTEDT T, KECKLUND G, KNUTSSON A. Spectral analysis of sleep electroencephalography in rotating three-shift work . Scand J Work Environ Health 1991;17:330-6. Fourteen male rotating threeshift workers were subjected to 24-h ambulatory polysomnographic recording in connection with morning, afternoon, and night shift work (at home and at work) . Total sleep time, stage 2, rapid-eye-movement sleep, and slow-wave sleep (stages 3 + 4) were significantly reduced during sleep in connection with the night and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(48 citation statements)
references
References 36 publications
4
42
0
2
Order By: Relevance
“…This also explains the obvious exhaustion of nurses following periods of nighttime working. Our results also indicated that the total duration of daytime sleep was a slightly shorter than that of nighttime sleep, which is consistent with several prior studies among healthy men (2,33,35,37). In other words, there is a tendency for the sleep quality of permanent night shift nurses to deteriorate and for them to develop a small, but cumulative, sleep deficit.…”
Section: Chung Et Alsupporting
confidence: 82%
See 1 more Smart Citation
“…This also explains the obvious exhaustion of nurses following periods of nighttime working. Our results also indicated that the total duration of daytime sleep was a slightly shorter than that of nighttime sleep, which is consistent with several prior studies among healthy men (2,33,35,37). In other words, there is a tendency for the sleep quality of permanent night shift nurses to deteriorate and for them to develop a small, but cumulative, sleep deficit.…”
Section: Chung Et Alsupporting
confidence: 82%
“…EEG delta-power is a characteristic of NREM and is used to define deep sleep (23). Several prior experimental studies have revealed that slow wave activity during periods of NREM sleep depends on prior waking time (33,35,36). As we found that the daytime sleep of permanent night shift nurses had lower sleep onset latency and significantly higher proportions of deeper sleep, we argue that they may have longer periods of restlessness and exhaustion before eventually falling asleep during the day, compared to at night.…”
Section: Chung Et Almentioning
confidence: 54%
“…Such findings highlight the need to examine the wider potential impact of quick returns. While the consequences of quick returns have been examined in previous reviews to some extent (Knauth 1996, Sallinen and Kecklund 2010, Kecklund and Åkerstedt 1995, Åkerstedt 2003, none of these reviews focused exclusively on quick returns and none used a systematic approach. The current study addresses these shortcomings by conducting a systematic literature search with the aim of consolidating the evidence on the relationship between quick returns and outcome measures ranging from health, sleep, functional ability and work-life balance.…”
Section: Introductionmentioning
confidence: 98%
“…Most disruptions are experienced in connection to N-shifts, day sleep is typically curtailed by 2-3 hours or more (Foret and Lantin, 1972;Tilley et al, 1982;Torsvall et al, 1981;Åkerstedt et al, 1991). Also morning (M)-shifts are associated with shortened and disturbed sleep (Folkard et al, 1989;Kecklund and Åkerstedt, 1995;Knauth et al, 1980;Torsvall et al, 1981;Åkerstedt et al, 1991;. The earlier the start time of the M-shift the shorter is the sleep, mainly because of the poor flexibility in adjusting the bed time to the start of the M-shift Foret and Lantin, 1972;Knauth et al, 1980).…”
Section: Problemsmentioning
confidence: 99%